1983
DOI: 10.1042/cs0650137
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Calcium Metabolism in Essential Hypertension

Abstract: Calcium metabolism has been investigated in patients with essential hypertension and normal renal function to evaluate the renal calcium handling and the reported increase in renal calcium loss. In 55 hypertensive and 55 sex- and age-matched healthy normotensive subjects creatinine clearance, serum total and ionized calcium, plasma parathyroid hormone and 24 h urinary excretion of calcium, sodium and cAMP were measured. In a subgroup of 20 hypertensive patients and 20 controls the fasting calcium excretion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
2
3

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(88 citation statements)
references
References 21 publications
7
76
2
3
Order By: Relevance
“…[1][2][3][4][5][6][7] Consistently, studies in hypertensive rats have shown that hypercalciuria and ensuing hyperparathyroidism lead to reduced growth and detectable decrease in total bonemineral content later in life. 8,9) Recently, it was also shown that higher blood pressure in elderly white women is statistically associated with increased bone loss at the femoral neck, which may contribute to bone fracture.…”
mentioning
confidence: 86%
“…[1][2][3][4][5][6][7] Consistently, studies in hypertensive rats have shown that hypercalciuria and ensuing hyperparathyroidism lead to reduced growth and detectable decrease in total bonemineral content later in life. 8,9) Recently, it was also shown that higher blood pressure in elderly white women is statistically associated with increased bone loss at the femoral neck, which may contribute to bone fracture.…”
mentioning
confidence: 86%
“…Apparently, the kidney in the offspring of hypertensive parents is less sensitive to PTH. Alternatively, the higher level of plasma intact PTH in the offspring of hypertensive parents may be viewed as secondary to a relative calcium deficiency, which could arise from a renal calcium leak as proposed by McCarron et al 13 and Strazullo et al 18 In the context of a decreased renal sensitivity to intact PTH , the level of 1,25-dihydroxyvitamin D 3 , activated by PTH in the kidney, can be regarded as inappropriately low in the offspring of hypertensive parents. More research on calcium metabolism in these groups of offspring is needed.…”
Section: Discussionmentioning
confidence: 99%
“…1, the BMD was significantly lower in WHT compared with WNT (0.595 ±0.019 g/cm 2 vs. 0.666±0.024 g/ cm 2 , p< 0.05). The T-score and Z-score were both significantly lower in WHT compared with WNT (p< 0.05, each).…”
Section: Bmdmentioning
confidence: 99%